Psychological Distress, Neuroticism, and Loneliness in Adolescents from Broken Homes - Sonia Patricia; Arthur Huwae (Bisma The Journal of Counseling, 2025)
The mental health landscape among Indonesian adolescents is showing an increasingly alarming trend. Data indicate that approximately 15.5 million adolescents, or 34.9% of that age group, are struggling with at least one form of mental health issue. Among the various problems faced, loneliness holds a crucial position as it not only affects emotional well-being but also significantly influences the social development of adolescents. This study was conducted to examine the role of psychological distress and neuroticism as predictor variables of loneliness among broken home adolescents in Indonesia. The research sample consisted of 485 adolescents aged 15-21 years from various regions across Indonesia, selected through purposive sampling. The study employed a quantitative approach using multiple linear regression analysis. The instruments used were the Kessler Psychological Distress Scale (K-10), the NEO Five Factor Inventory (NEO-FFI), and the De Jong-Gierveld Loneliness Scale (DJGLS). The findings showed that both the major and minor hypotheses were accepted. Psychological distress and neuroticism were found to be significant joint predictors of loneliness (F= 89.350 and Sig.= 0.000). Psychological distress was a significant positive predictor of loneliness (t = 8.058 and Sig.= 0.000), as was neuroticism (t = 6.030 and Sig.= 0.000). These results imply the necessity for comprehensive interventions to manage psychological distress and neuroticism in order to reduce loneliness among adolescents from broken homes.